Linear friction welding of Ti-6Al-4V: Modelling and validation - Turner, R; Gebelin, J; Ward, R; Reed, R (2011)
The linear friction welding (LFW) process - of the type required for the production of bladed discs for the next generation of civil aero-engines - is modelled using numerical and analytical methods. For model validation and testing, experimental work is carried out on the Ti-6Al-4V alloy using pilot-scale apparatus. Welds were instrumented with thermocouples to deduce the heat transfer effects prevalent in the process. The sensitivity of the measured rates of upset to the critical process variables - amplitude, frequency and the applied pressure - is shown to be consistent with the predictions of the modelling. The flash produced is dependent upon the ratio of oscillation amplitude to applied load; when this is large, a rippled morphology is produced. An analytical model of the process is proposed, in which the rate of mechanical working is balanced against the enthalpy associated with flash formation; at steady state, the temperature is predicted to decrease exponentially with distance in the heat-affected zone (HAZ), and the temperature gradient in the HAZ to increase as the upset rate increases, consistent with observation. By consideration of the form of the analytical model and the processes occurring during LFW it is suggested that, for a given upset rate, the weld temperature decreases as the pressure increases. Analysis of the experimental data indicates that the efficiency of adiabatic heating is close to 100%. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.